New Criticism and Reader-response Theory in Literary Criticism of the USA: Comparative Aspect - Anisimova, Lyudmyla (Pitannâ lìteraturoznavstva, 2013)
The aim of our research is to accomplish the comparative analysis of two powerful in the USA literary critical movements of XX century: New Criticism and Reader-Response Theory (paying attention more to the last one, less studied in Ukraine). Their features, main contradictions, common ideas, points of coincidence, reasons of emergence and decline, degree of influence to the development of theoretical and critical process and value for contemporary science are revealed. Though in majority of guides and glossaries pointed that Reader-Response Theory stands in total opposition to the hegemony of formalistic New Criticism and as the reaction to assay Affective fallacy of W. K. Wimsatt and Monroe Beardsley in late 1960th and early 70th in the USA. As we thought, exactly L. M. Rosenblatt (1904-2005) should considered to be the founder of denoted theory and her book “Literature as Exploration” (1938) as the pioneer work in reader-oriented criticism. It is interesting that both New critics and Reader-response theorists considered the book of I.A. Richards “Practical Criticism” (1929) as the important basis for their theories, but accenting different aspects. Therefore to a certain extent these theories from the beginnings have got common source, but different vectors of development and time of growth. In article the main classifications of RRT of N. N. Holland and L. M. Rosenblatt are represented, analyzed and compared. Also common and distinctive features of New Criticism and RRT are defined. In general the most suitable for practical use is L. M. Rosenblatt’s transactional theory of reading, in which the same attention is paid both to the reader and the text, and meaning is evoking during the process of transaction between them.